Postnatal maturation of somatostatin-expressing inhibitory cells in the somatosensory cortex of GIN mice - Kinnischtzke, Amanda K.; Sewall, Anna M.; Berkepile, Jon M.; Fanselow, Erika E. (Frontiers in Neural Circuits, 2012)
Postnatal inhibitory neuron development affects mammalian brain function, and failure of this maturation process may underlie pathological conditions such as epilepsy, schizophrenia and depression. Furthermore, understanding how physiological properties of inhibitory neurons change throughout development is critical to understanding the role(s) these cells play in cortical processing. One subset of inhibitory neurons that may be affected during postnatal development is somatostatin-expressing cells. A subset of these cells is labeled with green-fluorescent protein (GFP) in a line of mice known as the GIN line. Here, we studied how intrinsic electrophysiological properties of these cells changed in the somatosensory cortex of GIN mice between postnatal ages P11 to P32+. GIN cells were targeted for whole-cell current clamp recordings and ranges of positive and negative current steps were presented to each cell. The results showed that as the neocortical circuitry matured during this critical time period, multiple intrinsic and firing properties of GIN inhibitory neurons, as well as those of excitatory (regular-spiking [RS]) cells, were altered. Furthermore, these changes were such that the output of GIN cells, but not RS cells, increased over this developmental period. We quantified changes in excitability by examining the input-output relationship of both GIN and RS cells. We found that the firing frequency of GIN cells increased with age, while the rheobase current remained constant across development. This created a multiplicative increase in the input-output relationship in the GIN cells, leading to increases in gain with age. The input-output relationship of the RS cells, on the other hand, showed primarily an additive shift with age, but no substantial change in gain. These results suggest that as the neocortex matures, inhibition coming from GIN cells may become more influential in the circuit and play a greater role in the modulation of neocortical activity.